Kekuatan Alat Bukti E-mail Dalam Persidangan Perkara Perdata - Jihan Rizki Putri Permono; Merry Tjoanda; Pieter Radjawane (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The development of information technology right now introduced to the public by the existence of electronic evidence.Purposes of the Research: The purpose of this study is to discuss the strength of e-mail evidence in civil case trials in strengthening an argument in courtMethods of the Research: This research is a normative juridical research. This type of research is descriptive analysis. Focusing on an inventory of positive law, legal principles and doctrines, legal findings in cases in concreto, legal systematics, legal synchronization levels, legal comparisons and legal history.Results of the Research: Electronic evidence can have legal force if the information obtained guarantees its integrity, can be accounted for, and can be displayed so as to explain a situation. The regulation of electronic information and electronic documents is contained in Law no. 11 of 2008 concerning Information and Electronic Transactions (ITE) where this law is expressly declared valid as evidence in court, especially in civil courts and regulation no. 82 of 2012 concerning the implementation of electronic systems and transactions and reinforced by Article 5 paragraph 1 of the Electronic Information and Technology Law (UU ITE) that electronic information and/or electronic documents and/or their printed results are legal evidence.